Remembering the Host in Tuberculosis Drug Development. (21st December 2018) - Frank, Daniel J; Horne, David J; Dutta, Noton K; Shaku, Moagi Tube; Madensein, Rajhmun; Hawn, Thomas R; Steyn, Adrie J C; Karakousis, Petros C; Kana, Bavesh Davandra; Meintjes, Graeme; Laughon, Barbara; Tanvir, Zaid
Abstract : We discuss recent data and concepts important for development of host-directed therapies for tuberculosis that emerged from the "Strategic Discussion on Repurposing Drugs & Host Directed Therapies for TB" workshop organized by the Stop TB Working Group on New Drugs. Abstract: New therapeutics to augment current approaches and shorten treatment duration are of critical importance for combating tuberculosis (TB), especially those with novel mechanisms of action to counter the emergence of drug-resistant TB. Host-directed therapy (HDT) offers a novel strategy with mechanisms that include activating immune defense mechanisms or ameliorating tissue damage. These and related concepts will be discussed along with issues that emerged from the workshop organized by the Stop TB Working Group on New Drugs, held at the Gordon Research Conference for Tuberculosis Drug Development in Lucca, Italy in June 2017, titled "Strategic Discussion on Repurposing Drugs & Host Directed Therapies for TB." In this review, we will highlight recent data regarding drugs, pathways, and concepts that are important for successful development of HDTs for TB.